2002
DOI: 10.1007/s00429-002-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and distribution of gonadotropin-releasing hormone (GnRH) neuronal systems in the brain of the cichlid fish Cichlasoma dimerus

Abstract: Using immunocytochemistry we have described the distribution and ontogeny of three distinct gonadotropin-releasing hormone (GnRH) neural systems, emphasizing the analysis during the period of sex differentiation in the South American cichlid fish Cichlasoma dimerus. In the forebrain a group of neurones immunoreactive to salmon GnRH that formed clusters in the nucleus olfacto retinalis (NOR), was located at the junction of the olfactory bulb and the telencephalon. These neurones differentiated 3 days after fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
8
47
1
Order By: Relevance
“…When treated with rhFSH, 80% of the gonads were differentiated to presumptive ovaries, based on the morphological description available for this species (Meijide et al 2005). The results of this experiment reinforce our previous hypothesis about a correlation between the innervation of pituitary cells by GnRH1 fibers and the release of FSH that will be acting in any of the important steps of the sexual differentiation process (Pandolfi et al 2002).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When treated with rhFSH, 80% of the gonads were differentiated to presumptive ovaries, based on the morphological description available for this species (Meijide et al 2005). The results of this experiment reinforce our previous hypothesis about a correlation between the innervation of pituitary cells by GnRH1 fibers and the release of FSH that will be acting in any of the important steps of the sexual differentiation process (Pandolfi et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…A correlation between the innervation of the pituitary gland by GnRHI fibers and the onset of the sexual differentiation process was already reported for this species suggesting that GTHs may be involved in this process (Pandolfi et al 2002). The second aim of this study was to evaluate the effect of FSH on the gonadal differentiation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study no such migratory pattern was observed in the sbGnRH neurons with respect to both XX, XY fish. This is unlike in mammals but similar observations were made in some other cichlid fish like Cichlasoma dimerus (Pandolfi et al, 2002). It appears that in these fish a population of POA-H neurons originate in the POA-H itself or else migrate from some other cerebral or extra-cerebral region and start synthesis of GnRH (i.e.…”
Section: Discussionsupporting
confidence: 57%
“…In this context, the possibility that the hypothalamo-pituitary-gonadal axis is involved in triggering gonadal sex differentiation is currently under debate (see Fitzpatrick et al, 1993;Kah et al, 1993;Feist and Schreck, 1996;Baroiller and Guiguen, 2001;Miranda et al, 2001;Devlin and Nagahama, 2002;Pandolfi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%